STUDIES ON THERMAL DEFFUSIVITY AND CONDUCTIVITY OF FRESHWATER AND DRY FISH - ANNAMMA, T T; RAO, C V.N (Fishery Technology, 2017)
Thermal diffusivity (cr) and conductivity (K) of fresh and dry’ cured fish at different moisture levels were investigated by acalorimeter (regular regime) method and transient line source technique. Thermal conductivity has a linear correlation with packing density and percentage water content. K values calculated from formula method and line source technique are comparable